5m-5n+5m+5n When simplified: 10m
-7m - 3m + 5m = -5m
5m - 6 + m + 10 = 6m + 4
5m-3x+3m+2x 2m-x
It is simply: 5m+2
8m + 3n - 5m + 10n = 3m +13n
15m + 4n - 5m + 9n = 10m + 13n
3+4m+5m=214m+5m=21-39m=18m=18/9m=2
It is: 9m +8 -4m +7 -5m = 15
-5m-3+4 = 11 -5m = 11+3-4 -5m = 10 m = -2
-3m = 5m+8 -3m-5m = 8 -8m = 8 m = -1
To solve the equation 5m + 3 = 3m + 9, you need to isolate the variable m. Start by subtracting 3m from both sides to get 2m + 3 = 9. Then, subtract 3 from both sides to get 2m = 6. Finally, divide by 2 to find m = 3.